Day-by-Day Blood Pressure Variability and Functional Outcome After Acute Ischemic Stroke. Issue 7 (July 2015) - Fukuda, Kenji; Kai, Hisashi; Kamouchi, Masahiro; Hata, Jun; Ago, Tetsuro; Nakane, Hiroshi; Imaizumi, Tsutomu; Kitazono, Takanari; Ishitsuka, Takao; Fujimoto, Shigeru; Ibayashi, Setsuro; Kusuda, Kenji; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose— The relationship between blood pressure (BP) variability and functional outcome in patients with acute ischemic stroke remains unclear. This study aimed to elucidate whether in-hospital day-by-day BP variability is associated with functional outcome after acute ischemic stroke. Methods— Using the Fukuoka Stroke Registry, we included 2566 patients with a first-ever ischemic stroke who had been functionally independent before the onset and were hospitalized within 24 hours. BP was measured daily, and its variability was assessed by SD, coefficients of variance, and variations independent of mean. Poor functional outcome was assessed by modified Rankin Scale scores ≥3 at 3 months. Results— After adjustment for multiple confounding factors including age, sex, risk factors, stroke features, baseline severity, thrombolytic therapy, antihypertensive agents, and mean BP, day-by-day BP variability during the subacute stage (4–10 days after onset) was independently associated with a poor functional outcome (multivariable-adjusted odds ratios [95% confidence interval] in the top versus bottom quartile of systolic BP variability, 1.51 [1.09–2.08] for SD; 1.63 [1.20–2.22] for coefficients of variance; 1.64 [1.21–2.24] for variations independent of mean). Similar trends were also observed for diastolic BP variability. These trends were unchanged in patients who were not treated with antihypertensive drugs. In contrast, no association was found between indices of BP variability during the acute stage and functional outcome after adjusting for potential confounders. Conclusions— These data suggest that intraindividual day-by-day BP variability during the subacute stage is associated with the 3-month functional outcome after acute ischemic stroke.